Prenatal exercise (including but not limited to pelvic floor muscle training) and urinary incontinence during and following pregnancy: a systematic review and meta-analysis. Issue 21 (18th October 2018) - Davenport, Margie H; Nagpal, Taniya S; Mottola, Michelle F; Skow, Rachel J; Riske, Laurel; Poitras, Veronica J; Jaramillo Garcia, Alejandra; Gray, Casey E; Barrowman, Nick; Meah, Victoria L; Sobierajski, Frances; James, Marina; et al.
Abstract : Objective: To examine the relationships between prenatal physical activity and prenatal and postnatal urinary incontinence (UI). Design: Systematic review with random effects meta-analysis and meta-regression. Data sources: Online databases were searched up to 6 January 2017. Study eligibility criteria: Studies of all designs were included (except case studies) if they were published in English, Spanish or French and contained information on the Population (pregnant women without contraindication to exercise), Intervention (subjective or objective measures of frequency, intensity, duration, volume or type of exercise, alone ["exercise-only"] or in combination with other intervention components [e.g., dietary; "exercise + co-intervention"]), Comparator (no exercise or different frequency, intensity, duration, volume and type of exercise) and Outcome (prenatal or postnatal UI). Results: 24 studies (n=15 982 women) were included. 'Low' to 'moderate' quality evidence revealed prenatal pelvic floor muscle training (PFMT) with or without aerobic exercise decreased the odds of UI in pregnancy (15 randomised controlled trials (RCTs), n=2764 women; OR 0.50, 95% CI 0.37 to 0.68, I 2 =60%) and in the postpartum period (10 RCTs, n=1682 women; OR 0.63, 95% CI 0.51, 0.79, I 2 =0%). When we analysed the data by whether women were continent or incontinent prior to the intervention, exercise was beneficial at preventing the development of UI in women with continence, but not effective in treating UI in women with incontinence. There was 'low' quality evidence that prenatal exercise had a moderate effect in the reduction of UI symptom severity during (five RCTs, standard mean difference (SMD) −0.54, 95% CI −0.88 to –0.20, I 2 =64%) and following pregnancy (three RCTs, 'moderate' quality evidence; SMD −0.54, 95% CI −0.87 to –0.22, I 2 =24%). Conclusion: Prenatal exercise including PFMT reduced the odds and symptom severity of prenatal and postnatal UI. This was the case for women who were continent before the intervention. Among women who were incontinent during pregnancy, exercise training was not therapeutic.